Colchicine alleviates acute postoperative pain but delays wound repair in mice: Roles of neutrophils and macrophages. Issue 1 (November 2017) - Sukeishi, Asami; Isami, Koichi; Hiyama, Haruka; Imai, Satoshi; Nagayasu, Kazuki; Shirakawa, Hisashi; Nakagawa, Takayuki; Kaneko, Shuji
Background: Acute postoperative pain is induced by most incisional surgeries and usually resolves with wound repair. However, many patients experience moderate to severe pain despite receiving currently available postoperative pain relief. Accumulating evidence suggests that inflammatory cells, neutrophils, and macrophages infiltrating the wound site contribute to the acute inflammation, pain, and subsequent wound repair. Colchicine is commonly used to relieve pain in gout by inhibiting the infiltration of granulocytes and other motile cells. In this study, we examined the effects of colchicine on acute postoperative pain and wound repair by correlating the infiltration of neutrophils and macrophages in a mouse model of postoperative pain induced by plantar incision. Furthermore, these effects of colchicine were compared with clodronate liposomes, which selectively deplete circulating macrophages. Results: Plantar incision induced mechanical hypersensitivity in the ipsilateral hind paw that peaked one day and lasted for three days after the surgery. Treatment with colchicine significantly attenuated the early infiltration of Gr1-positive cells (neutrophils) around the incision site and mechanical hypersensitivity, which was accompanied with inhibition of the subsequent infiltration of Iba1-positive cells (macrophages) and macrophage polarization toward the proinflammatory M1 phenotype. By contrast, an intravenous injection of clodronate liposomes significantly inhibited the infiltration of macrophages around the incision site but had little effect on the infiltration of neutrophils or mechanical hypersensitivity. Importantly, colchicine treatment significantly delayed wound closure after the incisional surgery, whereas clodronate liposome administration had no effect on wound closure. Conclusion: These results suggest that colchicine can alleviate acute postoperative pain and also enhance the risk of delayed wound repair, which are associated with the suppression of neutrophil and subsequent proinflammatory M1 macrophage infiltration around the incision site, while the involvement of macrophages may be limited.